The Importance of Experimental Class in the Teaching-Learning Process for Deaf Students: An experience report in Professional and Technological Education (PTE) (Research, Society and Development, 2020)
Chemistry teaching for the deaf requires specific methodologies, mainly, which include visual experiences, with the possibility of using the Brazilian Sign Language - Libras through the professional Libras interpreter. In this context, the article aims to report an experience of teaching practice with a deaf student from the Sugar and Alcohol Manufacturing Assistant Course at SENAI School in Itumbiara-GO who used experimentation as a teaching method on the treatment of broth of cane for the manufacture of sugar and alcohol. The research is anchored in the theoretical assumptions of professional education in Figueiredo (2017), inclusive education in Mantoan (2003), experimentation in Gonçalves and Goi (2020) and teaching of the deaf (Quadros & Karnop, 2004), among others. The research methodology is qualitative, carried out through the observation of the teacher and field notes, as a method of data collection, allowing to perceive the learning of the deaf student during the execution of the experiment. The questions that include visual experiences occurred during practice, can conclude that experimental activities contribute to the learning process, focusing on deaf students.